Immunoglobulin G levels predicts risk of recurrent adverse cardiovascular events in myocardial infarction patients. Issue 6 (1st November 2020) - Hally, Kathryn E.; Holley, Ana S.; Kristono, Gisela A.; Harding, Scott A.; Larsen, Peter D.
Abstract: Background: Patients with myocardial infarction (MI) are at an increased risk of experiencing recurrent major adverse cardiovascular events (MACE) but predicting MACE has remained challenging. Immunoglobulins are implicated in cardiovascular disease, although the predictive value of total immunoglobulin G (IgG) has not yet been evaluated in a secondary prevention setting. This study examined whether total IgG is predictive of MACE in an MI population, and how total IgG compared to the predictive value of C-reactive protein (CRP), an acute inflammatory marker. Methods: We conducted a case–control study with 40 MI subjects (cases) who experienced MACE within 1 year of their index admission. Cases were matched for age, sex, diabetes and presentation with 77 controls who did not have MACE. Pre-discharge plasma samples were analysed for total IgG and CRP. Results: We observed higher levels of total plasma IgG in MI subjects with MACE (24.9 (16.2–43.7) mg/mL) compared to controls (18.4 (9.1–37.3) mg/mL; p < 0.05). Higher levels of IgG were associated with increased risk of MACE in our MI population. MI subjects within quartiles 3 and 4 of total IgG had 6 times and 4 times, respectively, the rate of MACE compared to subjects in quartile 1. There was no difference in CRP levels between cases and controls (1.1 (0.5–3.0) vs. 1.9 (0.6–6.1) mg/mL, p = 0.10), and no relationship was observed between CRP and MACE. Conclusion: Pre-discharge IgG level was a better marker for predicting MACE post-MI than CRP, which had no predictive value in this study.